2020
DOI: 10.18203/2320-1770.ijrcog20202737
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endometrial causes of postmenopausal bleeding with it's correlation with endometrial thickness and hysteroscopy findings and endometrial tissue histopathology

Abstract: Background: Postmenopausal bleeding (PMB)accounts for 5% of gynecology visit. All with unexpected uterine bleeding should be evaluated for endometrial carcinoma since this potentially lethal disease is the cause of bleeding in approximately 10 percent patients (range 1 to 25 percent, depending upon risk factors). The aim of the study was to evaluate endometrial causes of postmenopausal bleeding (PMB) with it's correlation with endometrial thickness (ET)and hysteroscopy findings and endometrial tissue histopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Bhangale et al also reported most (90%) cases between para 1 to para 4 and only one female (2%) as nulliparous. 9 In a study by Yela et al only (5%) females were nullipara. 7 In a study by Kaul et al (4%) females were nulliparous while (6%) were para >6.13.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Bhangale et al also reported most (90%) cases between para 1 to para 4 and only one female (2%) as nulliparous. 9 In a study by Yela et al only (5%) females were nullipara. 7 In a study by Kaul et al (4%) females were nulliparous while (6%) were para >6.13.…”
Section: Resultsmentioning
confidence: 93%
“…Study conducted by Bhangale et al revealed that most common endometrial cause of PMB was atrophic endometrium (44%). 9 The other causes were endometrial carcinoma (18%), endometrial hyperplasia (18%), endometrial polyp (12%), endometritis (4%), and leiomyoma (4%). The diagnostic accuracy of ET by TVS at a cut-off point of 5 mm was 94% with sensitivity 89.3%, specificity 100%, PPV 100% and NPV 88%.…”
Section: Resultsmentioning
confidence: 99%